2004
DOI: 10.1074/jbc.m309938200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Steps in Dislocation of Luminal Endoplasmic Reticulum-associated Degradation Substrates

Abstract: Dislocation of endoplasmic reticulum-associated degradation (ERAD) substrates from the endoplasmic reticulum (ER) lumen to cytosol is considered to occur in a single step that is tightly coupled to proteasomal degradation. Here we show that dislocation of luminal ERAD substrates occurs in two distinct consecutive steps. The first is passage across ER membrane to the ER cytosolic face, where substrates can accumulate as ubiquitin conjugates. In vivo, this step occurs despite proteasome inhibition but requires p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
106
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 65 publications
5
106
0
Order By: Relevance
“…By fractionating permeabilized proteasomeinhibited cells, we demonstrate that endogenous HMGR and a tagged version of its membrane region, as well as Insig-1-Myc, are released to the cytosol as full-length intact polypeptides. These results complement reports on the dislocation of luminal ERAD substrates (Rodighiero et al, 2002;Elkabetz et al, 2004;Afshar et al, 2005) and of membrane proteins with a single TMs (Huppa and Ploegh, 1997;Tortorella et al, 1998;Ye et al, 2003). Together with recent in vitro evidence for dislocation of ubiquitinated polytopic Ste6*p and Hmg2p (Garza et al, 2009) from yeast microsomes, it seems that, among the possible models suggested for dislocation of polytopic membrane ERAD substrates , complete extraction to the cytosol of intact polypeptide chains is a general feature of the delivery to the proteasome of this class of proteins.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…By fractionating permeabilized proteasomeinhibited cells, we demonstrate that endogenous HMGR and a tagged version of its membrane region, as well as Insig-1-Myc, are released to the cytosol as full-length intact polypeptides. These results complement reports on the dislocation of luminal ERAD substrates (Rodighiero et al, 2002;Elkabetz et al, 2004;Afshar et al, 2005) and of membrane proteins with a single TMs (Huppa and Ploegh, 1997;Tortorella et al, 1998;Ye et al, 2003). Together with recent in vitro evidence for dislocation of ubiquitinated polytopic Ste6*p and Hmg2p (Garza et al, 2009) from yeast microsomes, it seems that, among the possible models suggested for dislocation of polytopic membrane ERAD substrates , complete extraction to the cytosol of intact polypeptide chains is a general feature of the delivery to the proteasome of this class of proteins.…”
Section: Discussionsupporting
confidence: 58%
“…Not only is this process energetically expensive but also it challenges the cell to prevent these proteins from forming insoluble aggregates when the hydrophobic TMs are exposed to the hydrophilic environment of the cytosol. Indeed, specific AAA-ATPases, such as p97, and other molecular chaperones provide the driving force for dislocation and prevention of protein aggregation (Nishikawa et al, 2001;Ye et al, 2001;Elkabetz et al, 2004;Huyer et al, 2004;Bar-Nun, 2005;Buck et al, 2007;Lipson et al, 2008). The current study describes a system that should allow dissecting the steps in dislocation of polytopic ERAD substrates en route to proteasomal degradation and identification of cellular components that take part in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the autophagic/lysosomal inhibitors had minimal effect on either parameter. Indeed, parallel IB analyses of these 35 S-CYP3A immunoprecipitates with rabbit anti-Ub IgGs yielded the characteristic HMM ladders of polyubiquitylated CYP3A, which were dramatically enhanced in the presence of proteasomal, but not autophagic/lysosomal inhibitors, with marked accumulation observed at 6 h relative to the vehicle-treated cultures (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…1A). Accordingly, 35 S-radiometric quantitation of these CYP3A immunoprecipitates revealed that of the initial (0 h) 35 S-CYP3A content, 73.3 ± 39.2% remained at 1h, falling to 38.3 ± 16.1% at 6 h (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation